2020
DOI: 10.3390/cancers12020388
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage in Blood Leukocytes of Prostate Cancer Patients Undergoing PET/CT Examinations with [68Ga]Ga-PSMA I&T

Abstract: The aim was to investigate the induction and repair of radiation-induced DNA double-strand breaks (DSBs) as a function of the absorbed dose to the blood of patients undergoing PET/CT examinations with [68Ga]Ga-PSMA. Blood samples were collected from 15 patients before and at four time points after [68Ga]Ga-PSMA administration, both before and after the PET/CT scan. Absorbed doses to the blood were calculated. In addition, blood samples with/without contrast agent from five volunteers were irradiated ex vivo by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…Estimation of DSB frequency by means of these two dsDNA damage markers is a well-established approach 19 , 28 , 29 . In line with previous in vivo studies 18 , 20 we clearly observed the induction of DSBs by CT irradiation in significant excess over base line rate (p < 0.001), allowing the clear separation of irradiated and non-irradiated samples, which agrees with other SECT DSB studies 20 , 30 – 32 . With regard to single- and dual-energy CT irradiation modalities, the DSBs numbers induced were similar to each other (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Estimation of DSB frequency by means of these two dsDNA damage markers is a well-established approach 19 , 28 , 29 . In line with previous in vivo studies 18 , 20 we clearly observed the induction of DSBs by CT irradiation in significant excess over base line rate (p < 0.001), allowing the clear separation of irradiated and non-irradiated samples, which agrees with other SECT DSB studies 20 , 30 – 32 . With regard to single- and dual-energy CT irradiation modalities, the DSBs numbers induced were similar to each other (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…DNA double strand breaks (DSBs) were estimated by counting γ-H2AX + 53BP1 colocalizing foci in PBMCs 19 , 20 of three different probands in triplicates (Fig. 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…In diagnostic nuclear medicine applications, especially in longitudinal procedures, the role of radiobiology and the longterm consequences of radiobiology-related findings, such as reported in studies on DNA damage and repair, still has to be defined [95][96][97][98][99][100][101]. Currently, these studies provide no evidence that diagnostic nuclear medicine procedures are not safe.…”
Section: Position Of the Eanmmentioning
confidence: 99%
“…Finally, standardization of biological study protocols as well as depositing study data in repositories is required to allow comparison and combining of cohorts. Some publications, regarding both external and internal irradiation, indicate that there is a very low dose range (< 10 mGy) which shows a different dose response compared to higher doses [99,[104][105][106][107]. Therefore, extrapolating from higher absorbed doses and dose rates to very low doses and dose rates is not straightforward and needs further research.…”
Section: Essential Radiobiological Studiesmentioning
confidence: 99%
“…51 When compared with PET/CT, WB-MRI is faster to perform at a comparable cost, without the need for post-scan isolation precautions or potential side effects related to radiationinduced DNA damage. 52,53 In addition, WB-MRI offers more robust and almost a one-size-fits-all modality when compared with tracer-dependent PET imaging, thereby offering a valuable detection tool in many patients. A major advantage of WB-MRI is its local availability, eliminating the need to travel to specialist centers, with shorter visiting times to outpatient imaging facilities.…”
Section: Next-generation Imaging Modalitiesmentioning
confidence: 99%